2021
DOI: 10.3389/fchem.2021.631571
|View full text |Cite
|
Sign up to set email alerts
|

A Bifunctional Nanosilver-Reduced Graphene Oxide Nanocomposite for Label-Free Electrochemical Immunosensing

Abstract: A bi-functional material based on silver nanoparticles (AgNPs)-reduced graphene oxide (rGO) composite for both electrode modification and signal generation is successfully synthesized for use in the construction of a label-free electrochemical immunosensor. An AgNPs/rGO nanocomposite is prepared by a one-pot wet chemical process. The AgNPs/rGO composite dispersion is simply cast on a screen-printed carbon electrode (SPCE) to fabricate the electrochemical immunosensor. It possesses a sufficient conductivity/ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…However, a further increase in pH from 7.4 to 9 gradually diminishes the peak current. Since an acidic and basic pH medium causes denaturing of antibodies immobilized at the electrode surface, such denatured antibodies result in a lower current response. , Hence, the PBS of pH 7.4 is considered to be a highly suitable redox electrolyte. In addition, the pH of 7.4 corresponds to the pH of blood; therefore, the PBS of pH 7.4 was chosen for immunosensing purposes.…”
Section: Resultsmentioning
confidence: 99%
“…However, a further increase in pH from 7.4 to 9 gradually diminishes the peak current. Since an acidic and basic pH medium causes denaturing of antibodies immobilized at the electrode surface, such denatured antibodies result in a lower current response. , Hence, the PBS of pH 7.4 is considered to be a highly suitable redox electrolyte. In addition, the pH of 7.4 corresponds to the pH of blood; therefore, the PBS of pH 7.4 was chosen for immunosensing purposes.…”
Section: Resultsmentioning
confidence: 99%
“… (a) Scheme for preparation process of the typical sandwich‐type electrochemical immunosensors, in which N atom‐doped graphene (NGR) functionalized with hollow porous Pt‐skin Ag−Pt alloy (HP−Ag/Pt/NGR) and Au nanoparticles modified polypyrrole/poly (3,4‐ethylenedioxythiophene) nanotubes were fabricated as the signal amplifier and the substrate, respectively [88]. (b) Scheme for the fabrication of AgNP/rGO‐based label‐free electrochemical immunosensor [100]. (c) Schematic diagram of the preparation of zeolitic imidazolate frameworks and gold nanoparticle modified reduced graphene oxide (Au@ZIF‐8@rGO)‐based electrochemical immunosensor and the detection of glial fibrillary acidic protein (GFAP) [99a].…”
Section: Fabrication Of Graphene‐based Biosensorsmentioning
confidence: 99%
“…When approaching the use of more advanced nanomaterials in building efficient biosensors, proteins, enzymes and antibodies are largely considered as their intrinsic biochemical and structural features make them ideal candidates to assemble hybrid composites while keeping useful properties such as enzymatic activities, self-assembly behavior and biorecognition. As a first example, Chanarsa et al [ 69 ] reported a AgNPs-reduced GO composite as a component of an electrochemical immunosensor able to detect the immunoglobulin G as a model biomarker in blood serum ( Figure 7 ). In their study, the authors realized an AgNPs-reduced GO composite from a heat-assisted wet chemical reduction that can be easily deposited onto a screen-printed carbon electrode and used as support for adsorption of unfunctionalized antibodies specific for immunoglobulin G (IgG).…”
Section: Biosensors Based On Hybrid Biomolecules-nanomaterials Compos...mentioning
confidence: 99%
“… Electrochemical immunosensor for immunoglobulin G in blood serum. Screen-printed carbon electrodes are coated with AgNPs-reduced GO composites linked to antibodies specific for immunoglobulin G. Image adapted from [ 69 ] with permission of Frontiers, 2021. …”
Section: Figurementioning
confidence: 99%